دلالات الغياب في سورة الكوثر دراسة في دلالة غياب المخرج الحنجري والأصوات المطبقة - محلو, عادل (University of Eloued جامعة الوادي, 2017)
تُعدّ التقابلات الثنائية واحدة من أهمّ أدوات التحليل اللساني المعاصر التي طبّقت على دراسة النصوص الأدبية وغيره، وامتدّ تطبيقها حتىّ إلى مجالات أخرى كالأنثروبولوجيا مثلا. وتسعى هذه الدراسة إلى استثمار هذه الأداة للكشف عن الدلالات التي تؤدّيها المكوّنات اللسانية الغائبة في سورة الكوثر، وذلك من خلال غياب المخرج الحنجري في الآية الثانية، وغياب صفة الإطباق في الآية الثالثة، على أن يتمّ ذلك في ضوء استدعاء القطب الثاني من هذا التقابل الثنائي، وهو:"الحضور"؛ حيث يُستعان بحضور المخرج الحنجري في الآيتيْن الأولى والثالثة من السورة لإبراز دلالة غيابه في الآية الثانية، ويُستعان بدلالات حضور صفة الإطباق في الآيتْين الأولييْن لكشف دلالات غيابها في الآية الثالثة من سورة الكوثر. Considered as one of the main analysis devices used in contemporary linguistics, binarism opposition is not only applied on literary texts, but on other fields too as; Anthropology studies. This study, by using binarism opposition, aims at investigating the meaning behind the absence of some linguistic devices in Surah Al-Kawthar, in which there is an absence of vocal folds and velarization in the second and third verses respectively. On this base, the work uses the second part of the binary opposition to analyse the presence of vocal folds in the first and third verses of Surah Al-Kawthar and to justify the meaning of its absence in the second verse. The study also relies on the presence of velarization in the two first verses to understand the meaning behind its absence in the third verse.
Keywords: سورة الكوثر، المخرج الحنجري، الغياب; Surah Al-Kawthar, vocal folds, Absence